Gallaecia gothica : from the conspiracy of Dux Argimundus (AD 589/590) to integration in the visgothic kingdom of Toledo - Barroso Cabrera, Rafael, (Access archaeology., 2023)
'Gallaecia Gothica' offers a new interpretation of the Argimundus rebellion, one of the most difficult challenges of Reccared's reign. There are no specific details of how the conspiracy came about, but the throne was seriously threatened. The Chronicle of John of Biclaro underlined the gravity of this menace in his description of the punishment suffered by the rebel and his collaborators. His categorical condemnation of the attempted overthrow of the monarch is unlike that given to any other uprising narrated in the Chronicle, and it shows the importance that the abbot of Biclaro gave it in his narration.